EVALUASI ASPEK TRANSPORTASI TEMPAT PERISTIRAHATAN DI KM 97 TOL CIPULARANG - Setyarini, Ni Luh Putu Shinta; Linggasari, M.I. Dewi; Susanto, Hendra (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2019)
The density of the vehicle and the length of trip on the Cipularang Toll Road (around 57.5 km) can make the driver feel bored and decrease concentration. Driving a vehicle in a saturated state can endanger yourself and others. The decrease in concentration can cause unfavorable views, causing accidents. So resting is one of the most important needs in driving. In accordance with Government Regulation No.15 of 2005, regarding the technical requirements of toll road construction, that there must be a place of rest and services for the benefit of toll road users at least 1 for every 50 km distance in each direction. The presence of the KM 97 resting place in Cipularang Toll Road can help drivers and passengers to meet all their personal needs. The problem is how the manager of the resort serves visitors to meet the needs of the resort. Minimum Service Standards (SPM) are guidelines that govern the standards of resort services. Each resort does not necessarily have the same facilities and services. Therefore it is necessary to evaluate the facilities and services of the Cipularang Toll KM 97 resting place. The method to be used is the measurement of service quality with the importance performance analysis (IPA) method. Parking needs on Sundays = 375 vehicles> rather than parking capacity = 321 available vehicles. The level of satisfaction of respondents to all points regarding the reliability of the infrastructure of the resort both in terms of aspects of transportation and service facilities get a value of 80.32% which means very good. AbstrakPadatnya kendaraan dan lamanya perjalanan di ruas jalan Tol Cipularang (sekitar 57,5 km) dapat membuat pengemudi merasa jenuh dan menurunnya konsentrasi. Mengemudikan kendaraan dalam keadaan jenuh dapat membahayakan diri sendiri dan orang lain. Turunnya konsentrasi dapat menyebabkan pandangan yang kurang baik sehingga menimbulkan kecelakaan. Jadi istirahat merupakan salah satu kebutuhan yang sangat penting dalam berkendara. Sesuai PP No.15 tahun 2005, tentang persyaratan teknis pembangunan jalan tol, bahwa harus tersedia tempat istirahat dan pelayanan untuk kepentingan pengguna jalan tol paling sedikit 1 untuk setiap jarak 50 km setiap jurusan. Hadirnya tempat peristirahatan KM 97 di Tol Cipularang dapat membantu pengemudi dan penumpang untuk memenuhi segala kebutuhan pribadi. Permasalahannya adalah bagaimana pengelola dari tempat peristirahatan melayani pengunjung untuk memenuhi kebutuhan di tempat peristirahatan. Standar Pelayanan Minimal (SPM) adalah pedoman yang mengatur standar dari pelayanan tempat peristirahatan. Setiap tempat peristirahatan belum tentu memiliki fasilitas dan pelayanan yang sama. Oleh sebab itu perlu dilakukan evaluasi terhadap fasilitas dan pelayanan tempat peristirahatan KM 97 Tol Cipularang. Metode yang akan digunakan adalah pengukuran kualitas layanan dengan metode importance performance analysis (IPA). Kebutuhan parkir pada hari Minggu = 375 kendaraan > daripada kapasitas parkir = 321 kendaraan yang tersedia. Tingkat kepuasan responden terhadap seluruh poin mengenai keandalan dari infrastruktur tempat peristirahatan baik dari segi aspek transportasi maupun fasilitas pelayanan mendapatkan nilai sebesar 80,32% yang berarti sangat baik.